Strategies for Developing Afrocentric Career Coaching Programmes for Neurodiverse College Students - Otu, Mkpoikanke Sunday; Sefotho, Maximus Monaheng (International Journal of Research in Counseling and Education, 2024)
The objective of this study was to find out the strategies that would be effective for developing Afrocentric career coaching programmes for neurodiverse college students. As part of the qualitative research design, semi-structured interviews and focus group discussions were conducted. The participants of this study were six Counselling Psychology lecturers and six Special Needs Education lecturers who specialize in career coaching and development, located in Nigerian universities. The were selected using purposive sampling. To ensure validity and reliability, a semi-structured interview guide was developed and pilot-tested with a subset of participants. The guide included open-ended questions to explore participants' experiences, insights, and recommendations for developing Afrocentric career coaching programmes for neurodiverse college students. The data collection procedure consisted of structured individual interview sessions with each participating lecturer. In addition to the individual interviews, focus group discussions were conducted with a group of eight participants. These discussions provided an opportunity for participants to share their experiences and ideas collectively. The interviews and focus group discussions were also audio-recorded and transcribed verbatim for analysis. Thematic analysis was utilized to analyze the collected data. The transcripts were read and reread to identify recurring themes, patterns, and insights related to the development of Afrocentric career coaching programmes for neurodiverse college students. The findings of this study indicate that there are several strategies that can be considered when designing Afrocentric career coaching programmes for neurodiverse college students. These strategies include cultural sensitivity, representation, individualized approach, collaborative partnerships, skills development, and career exploration. The findings suggest that incorporating Afrocentric values and perspectives into career coaching can greatly enhance the effectiveness and inclusivity of such programmes. The findings of this study provide useful insights into the development of effective Afrocentric career coaching programmes for neurodiverse college students. The major contribution of this study is the development of Afrocentric framework for career coaching.